New Speakers in the Irish Context: Heritage Language Maintenance Among Multilingual Migrants in Dublin, Ireland - Diskin, Chloé (Frontiers in Education, 2020)
A migrant ‘boom’ in Ireland in the 2000s led to a 143% increase in non-Irish nationals, marking a shift from the country’s predominantly monocultural past, to a future that is multicultural and, by extension, multilingual. This report focuses on the Polish and Chinese communities in Dublin, Ireland, investigating individuals’ and families’ attitudes towards heritage language maintenance and transmission, and the strategies and practices they employed. Drawing on recorded semi-structured interviews with 45 migrants, a qualitative content analysis reveals that heritage language maintenance is of paramount importance, both for first and second generation migrants. Many parents send their children to weekend schools. Differences emerge, however, in the two communities’ views of the utility and value of the heritage language. Polish migrants’ discourse centres on the importance of the language for sustaining ties with extended family, particularly when return migration is a possibility; whereas Chinese migrants focus on the economic benefits of competence in Chinese, which is viewed as a passport to more attractive job opportunities in Asia. All participants report using their heritage language on a daily basis, and place strong emphasis on maintaining literacy, through print and digital media. Social media sites also enable migrants to communicate through their heritage language and maintain a sense of community, either through direct interaction or “passive monitoring” of others. This global inter-connectedness allows migrants to view their linguistic competence not as bilingualism per se, but as a repertoire of “mobile resources”, significantly widening the scope of what could be termed a ‘digital classroom’.